Democracy through learner-centered education: A Turkish perspective - YILMAZ, KAYA (My University, 2009)
Aimed at documenting the problems and constraints confronting learner-centered instruction in Turkey, this article first explains the link between democracy and education and the role of learner-centered instruction in realizing democratic ends. By drawing on John Dewey's ideas and Turkish scholars' perspectives on Turkish education, the article then presents the problems and constraints that pose threats to the implementation of learner-centered instruction in Turkey. The author also explains the problems within the Turkish educational system and teacher education programmes, and the challenges that in-service teachers and students may experience with learner-centered instruction. © Springer Science+Business Media B.V. 2008.